Agility and resource dependency in ramp-up process of humanitarian organizations. Issue 3 (12th August 2019) - Lu, Qing; Wu, Jie; Goh, Mark; De Souza, Robert
Abstract : Purpose: The ramp-up in humanitarian logistics operations is a stage when the demand surges, often at the start of an emergency. In response, agility is a key strategy used by the humanitarian organizations (HOs). However, the HOs are constrained by their existing resources and have to respond in the ramp-up process under their resource dependency. The purpose of this paper is to develop a framework on agility-building strategies used by HOs for the ramp-up. Design/methodology/approach: This study applies both the dynamic capabilities perspective and resource dependence theory to humanitarian relief operations, and develops four testable propositions to explore the agility-building strategies of the HOs for the ramp-up process. A multiple-case study is conducted on six international HOs operating in Indonesia to verify them, in addition to an extensive literature search. Findings: The case study shows that the human resource management, pre-positioning, standardization and supplier management of the HOs are all related to their resources and environment in the ramp-up process. The authors highlight the practical differences between the few super large, resource rich and centralized HOs with the second-tier HOs. Research limitations/implications: Given the small sample size and single country as the site of study, some findings may not be applicable to the other HOs or in other regions. Practical implications: The propositions could be applicable to other HOs operating under similar environments, and potentially to the commercial enterprises operating in a highly volatile environment with severe resource scarcity. Originality/value: This study provides new insights into ramp-up operations and into how HOs build their agility and reduce their resource dependencies. Theoretically, the paper applies two established theories in the strategic management literature to a new field.